EPISTEMOLOGI PEMBELAJARAN BAHASA ARAB KOMUNIKATIF: TELAAH PEDAGOGIS, ANDRAGOGIS, DAN HEUTAGOGIS - Musgamy, Awaliah (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2020)
Communicative Arabic learning is an Arabic learning approach that places Arabic as its basic function as a means of communication. In its implementation, Arabic learning is a continuous process starting from pedagogical, andragogical, and heutagogical learning which cannot be separated from the four components of epistemology which in this case include sources, structures, methods and validity. Through the epistemology of communicative Arabic learning which is examined through pedagogical, andragogical, and heutagogical, it is seen that the Arabic learning process needs to be done by positioning Arabic learning as a constructive process in directing students to be able to communicate actively.